PENGARUH HARGA, PRODUK, PROMOSI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO FURNITURE MEDIA JEPARA DI CIBINONG KABUPATEN BOGOR - Mujito; Muchammad Hamdani; Ananda Oktaviana (Institut Teknologi dan Bisnis Dewantara, 2025)
This study aims to determine the effect of Price, Product, Promotion, and Location partially and simultaneously on Purchase Decisions at Media Jepara Furniture Store in Cibinong, Bogor Regency. The results of this study concluded that (1) The hypothesis results show that the price variable has a positive and significant effect on purchase decisions with a calculated t-value of 2.021 ˃ the table t-value of 1.984 and a significance value of 0.046 ˂ 0.10. (2) The product variable has a positive and significant effect on purchase decisions with a calculated t-value of 3.853 ˃ the table t-value of 1.984 and a significance value of 0.000 ˂ 0.10. (3) The promotion variable has a positive and significant effect on purchase decisions with a calculated t-value of 2.298 ˃ the table t-value of 1.984 and a significance value of 0.024 ˂ 0.10. (4) The location variable has a positive and significant effect on purchase decisions with a calculated t-value of 2.056 ˃ t-table value of 1.984 and a significance value of 0.042 ˂ 0.10. (5) Based on this study, all variables, namely price, product, promotion, and location, simultaneously have a positive and significant effect on purchase decisions with F-calculated ˃ F-table (61.616 ˃ 2.467) and a significance level of 0.000 ˂ 0.10. (6) Based on this study, the variable that has the most dominant effect on purchase decisions is the product variable.